Prenatal PUFA undernutrition and risk of adult psychiatric disorders (Bangladesh Journal of Medical Science, 2016)
The developing fetus requires significant amounts of poly unsaturated fatty acids (PUFAs/ FAs) to maintain its normal cellular growth and integrity. Suboptimal intrauterine conditions, including poor PUFAs nutrition, during critical periods of growth may lead to lifelong changes in the bodys organs and tissues, thus providing a physiological basis for adultonset disease. However, the Developmental Origins of Health and Disease (DOHaD) model provide a structure to assess the effect of early nutrition and growth on long-term health. Epidemiological statistics shows that when pregnant mothers experienced malnutrition or famine (e.g. the Dutch Hunger Winter of 1944-1945 and the Chinese famine of 1959-1961), the risk of developing metabolic and psychiatric disease in their children increased. The theory of DOHaD is well referenced in the understanding of adult metabolic diseases, but less so in the field of psychiatric disorders. As PUFAs play critical roles in brain development, considerable effort has been taken in elucidating their function in the pathogenesis of neuropsychiatric disorders.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.313-319